The Effect of Leverage, Profitability, Liquidity, and Firm Size on Earnings Quality (Empirical Study on the Hotel Sub-Sector Service Company, Restaurant & Tourism on the Indonesia Stock Exchange for the period 2016-2020) - Bimo, Antonius; Putri, Anike; Sulaksana, Hesti Hesnawati (Research Collaboration Community (Rescollacom), 2024)
Earnings quality reflects how much the company's profits are presented in accordance with the company's circumstances in that year. The better disclosure is done by the company would affect greater quality of profits owned by the company. This caused by the concept of transparency. Segment information is needed by users of financial statements to see the economic characteristics of each segment within the company. The dependent variable in this study is earnings quality, the independent variables are leverage, profitability, liquidity, and company’s size. This research is a type of quantitative research using companies’ financial statements. Total samples collected are 70 financial statements comes from 14 company. The sampling method is purposive sampling method. The results of this study indicate that leverage, profitability, and firm size partially affect earnings quality. Meanwhile, liquidity has no effect on earnings quality. The leverage, profitability, liquidity, and company size simultaneously affect the earnings quality in the hotel, restaurant and tourism sub-sectors listed on the IDX for the 2016-2020 period.